Correction to: Novel mutations in KMT2B offer pathophysiological insights on childhood-onset progressive dystonia - Dafsari, Hormos Salimi; Sprute, Rosanne; Wunderlich, Gilbert; Daimagüler, Hülya-Sevcan; Karaca, Ezgi; Contreras, Adriana; Becker, Kerstin; Schulze-Rhonhof, Mira; Kiening, Karl; Karakulak, Tülay; Kloss, Manja; Horn, Annette; et al. (Journal of human genetics, 2019)
Rapid progress has recently been made in the elucidation of the genetic basis of childhood-onset inherited generalized dystonia (IGD) due to the implementation of genomic sequencing methodologies. We identified four patients with childhood-onset IGD harboring novel disease-causing mutations in lysine-specific histone methyltransferase 2B gene (KMT2B) by whole-exome sequencing. The main focus of this paper is to gain novel pathophysiological insights through understanding the molecular consequences of these mutations.The disease course is mostly progressive, evolving from lower limbs into generalized dystonia, which could be associated with dysarthria, dysphonia, intellectual disability, orofacial dyskinesia, and sometimes distinct dysmorphic facial features. In two patients, motor performances improved after bilateral implantation of deep brain stimulation in the globus pallidus internus (GPi-DBS). Pharmacotherapy with trihexyphenidyl reduced dystonia in two patients.We discovered three novel KMT2B mutations. Our analyses revealed that the mutation in patient 1 (c.7463 A > G, p.Y2488C) is localized in the highly conserved FYRC domain of KMT2B. This mutation holds the potential to alter the inter-domain FYR interactions, which could lead to KMT2B instability. The mutations in patients 2 and 3 (c.3602dupC, p.M1202Dfs*22; c.4229delA, p.Q1410Rfs*12) lead to predicted unstable transcripts, likely to be subject to degradation by non-sense mediated decay.Childhood-onset progressive dystonia with orofacial involvement is one of the main clinical manifestations of KMT2B mutations. In all, 26% (18/69) of the reported cases have T2 signal alterations of the globus pallidus internus, mostly at a younger age. Anticholinergic medication and GPi-DBS are promising treatment options and shall be considered early.An amendment to this paper has been published and can be accessed via a link at the top of the paper.